1992
DOI: 10.2307/2159211
|View full text |Cite
|
Sign up to set email alerts
|

Integral Overrings of Two-Dimensional Going-Down Domains

Abstract: Abstract.It is proved that if R is a 2-root closed two-dimensional going-down domain with no factor domain of characteristic 2, then each integral overling of R is a going-down domain. An example is given to show that the "2-root closed" hypothesis cannot be deleted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…By applying the classical D + M construction (as in [26]) to such examples, it was shown in [13] that an overring of a going-down domain need not be a going-down domain. In fact, by an iterated pullback construction, it was shown in [19] that an integral overring of a going-down domain need not be a going-down domain. (Earlier, it had been shown that each integral overring of a going-down domain is a going-down domain if dim v (R) ≤ 2 [14] or if R is both locally divided and locally finite-conductor [ [3,Theorem 10].…”
mentioning
confidence: 99%
“…By applying the classical D + M construction (as in [26]) to such examples, it was shown in [13] that an overring of a going-down domain need not be a going-down domain. In fact, by an iterated pullback construction, it was shown in [19] that an integral overring of a going-down domain need not be a going-down domain. (Earlier, it had been shown that each integral overring of a going-down domain is a going-down domain if dim v (R) ≤ 2 [14] or if R is both locally divided and locally finite-conductor [ [3,Theorem 10].…”
mentioning
confidence: 99%